Results of sclerotherapy and mucopexy with haemorrhoidal dearterialization in II and III degree haemorrhoids. A 4 years' single centre experience - Lobascio, Pierluigi; Laforgia, Rita; Pezzolla, Angela (Frontiers in Surgery, 2023)
INTRODUCTION: Haemorrhoidal disease (HD) affects a considerable portion of the adult population. The aim of this study is to confirm the safety and efficacy of the treatments and to report the long-term outcomes of Sclerotherapy (ST) and Mucopexy and Haemorrhoidal Dearterialization (MHD) performed over the last 4 years in a single tertiary centre. The secondary outcome is to evaluate the usefulness of both techniques and to demonstrate how those can be associated as a bridge to surgery. MATERIALS AND METHODS: Patients affected by second–third-degree haemorrhoids and undergoing ST or non-Doppler guided MHD between 2018 and 2021 were enrolled. Safety and efficacy, recurrence rate, Haemorrhoid Severity Score (HSS) and pain resulting from both techniques were evaluated. RESULTS: Out of 259 patients, 150 underwent ST. Further, 122 (81.3%) patients were male and 28 (18.7%) were female. The mean age was 50.8 (range 34-68) years. Most of the patients (103, 68.6%) were affected by second-degree HD, while 47 (31.4%) were affected by third-degree HD. The overall success rate was 83.3%. The median pre-operative HSS score was 3 (IQR 0-4, p=0.04) and at 2 year the median HSS was 0 (IQR 0-1, p=0.03). No intraoperative complications and no drug-related side effects occurred. The mean follow-up for ST was 2 years (range 1-4; SD ±0.88). MHD was performed on 109 patients. In detail, 80 patients (73.4%) were male while 29 patients (26.6%) were female. The mean age in this group was 51.3 (range 31-69). Further, 72 patients (66.1%) were affected by third-degree HD and 37 (33.9%) by second-degree HD. The median HSS score was 9 (IQR 8-10, p=0.001) preoperatively two years after treatment was 0 (IQR 0-1, p=0.004). Major complications occurred in three patients (2.75%). The overall success rate was 93.5% (second degree 89.2% versus third degree 95.8%). The mean follow-up for MHD was 2 years (range 1-4; SD ±0.68). CONCLUSIONS: The results confirm the usefulness of those techniques, which can be considered safe and easily repeatable procedures, with a low recurrence rate after 2 years of median follow-up.